A Review on the Construction of Carbon-Based Metal Compound Composite Cathode Materials for Room Temperature Sodium-Sulfur Batteries - Wang, Xueyu; Guo, Daying; Yang, Lin; Jin, Minghuan; Chen, Xi’an; Wang, Shun (Frontiers in Chemistry, 2022)
Room temperature sodium-sulfur batteries are one of the most attractive energy storage systems due to their low cost, environmental friendliness, and ultra-high energy density. However, due to the inherent slow redox kinetics and the shuttle of polysulfides, the road to practical application is still full of difficulties. As a sulfur cathode, which is directly related to battery performance, a lot of research efforts have been devoted to it and many strategies have been proposed to solve the shuttle effect problem of sulfur cathodes. This paper analyzes the existing problems of sodium-sulfur batteries, that is, the solutions, mainly discusses and summarizes the direction of constructing carbon-based cathode materials for sodium-sulfur batteries, and elucidates the current research hotspots from two major directions. That is to construct advanced cathode materials based on two mechanisms of adsorption and electrocatalysis. Finally, the research direction of advanced sodium-sulfur batteries is prospected.